FORMULATION AND ANTIBACTERIAL ACTIVITY TEST OF THE PREPARATION CROWN ETHANOL EXTRACT SHOWER GEL PINEAPPLE (Apineapple comosus (L.) Merr) AGAINST BACTERIA Staphylococcus aureus - Christica Ilsanna Surbakti; Trinitatis Talunohi (FORTE JOURNAL, 2024)
Antibacterial bath soap is in great demand by the public. This is because it is believed to cleanse the skin and can also treat or prevent diseases caused by bacteria. One of the natural ingredients that are efficacious as a natural anti-bacterial is pineapple crown. Pineapple crown extract has secondary metabolites namely alkaloids, flavonoids, tannins, saponins and triterpenoids/steroids. The purpose of this study was to determine the formulation of liquid bath soap preparations with the use of pineapple crown ethanol extract (ananas comosus (l.) Merr) as liquid bath soap and to determine the potential of pineapple crown ethanol extract liquid bath soap (ananas comosus (l.) Merr) to have antibacterial properties against staphylococcus aureus bacteria. The type of research carried out is an experimental method. The work procedure consists of sample preparation, sample identification, simplisia making, characteristic examination, phytochemical screening, extract making, making liquid shower soap preparations, evaluating liquid shower soap preparations and antibacterial activity tests against staphylococcus aureus bacteria. Pineapple crown ethanol extract is formulated in a shower soap preparation whose formulation uses concentrations of 3%, 5% and 7%. The results of the characterization of pineapple crown simplisia showed a moisture content of 9.50%, water-soluble juice content of 19.88%, soluble juice content in ethanol 13.30%, total ash content of 6.76%, acid insoluble ash content of 1.19%. The results of phytochemical screening testing show pineapple crown contains alkaloids, flavonoids, tannins, saponins, triterpenoids/steroids.